Evaluation of the Rationality of Appropriate Doses of Corticosteroid Drugs in Patients With Nephrotic Syndrome in Hospitals - Susan Sintia Ramdhani; Nurhidayati Harun; Tina Marlina (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2022)
Nephrotic syndrome is a kidney disease in which symptoms include massive proteinuria, hypoalbuminemia, edema, and hyperlipidemia. Nephrotic syndrome has first-line therapy using corticosteroids. The purpose of this study was to determine the accuracy of the dose in patients with nephrotic syndrome. The method used in this study is a qualitative descriptive method of retrospective data acquisition by taking a sample population of nephrotic syndrome patients at the Outpatient Installation of General Hospital of Ciamis District Period January-July 2020. Descriptive analysis includes the accuracy of the dose guided by the management of Kidney Disease: Improving Global Outcomes (KDIGO) which is presented in the form of tables and narratives. The results of this study indicate that the ratio between men and women is 3:1 with those under 15 years old. There were 18 cases of nephrotic syndrome using corticosteroid therapy. The most widely used corticosteroids were methylprednisolone 61.1% (11 patients) and prednisone 38.9% (7 patients). The use of the dose in 18 cases of nephrotic syndrome was stated to be the right dose (100%) and in accordance with the management recommendations.